2007
DOI: 10.1038/sj.ejcn.1602690
|View full text |Cite
|
Sign up to set email alerts
|

Estimating resting energy expenditure in patients requiring nutritional support: a survey of dietetic practice

Abstract: Estimation of resting energy expenditure (REE) involves predicting basal metabolic rate (BMR) plus adjustment for metabolic stress. The aim of this study was to investigate the methods used to estimate REE and to identify the impact of the patient's clinical condition and the dietitians' work profile on the stress factor assigned. A random sample of 115 dietitians from the United Kingdom with an interest in nutritional support completed a postal questionnaire regarding the estimation of REE for 37 clinical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The overestimation of the severity of metabolic stress may have led to the application of higher stress factors to energy prescription in our cohort. A wide range of stress factors are incorporated into the estimates of energy requirements in an attempt to account for the increased energy burden of hypermetabolic states (37). However, these factors are applied inconsistently in clinical practice and the reasons for choosing a particular stress factor in individual cases are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The overestimation of the severity of metabolic stress may have led to the application of higher stress factors to energy prescription in our cohort. A wide range of stress factors are incorporated into the estimates of energy requirements in an attempt to account for the increased energy burden of hypermetabolic states (37). However, these factors are applied inconsistently in clinical practice and the reasons for choosing a particular stress factor in individual cases are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Energy requirements were calculated using the Henry equation , with the addition of appropriate stress and activity factors. A 10% stress factor was given for infection in the absence of pneumonia and septicaemia to reduce overestimation. Protein requirements were calculated from estimated nitrogen requirements .…”
Section: Methodsmentioning
confidence: 99%
“…Energy requirements were calculated using the Henry equation (24) , with the addition of appropriate stress and New menu with main meal at lunchtime and a lighter, bistro-style evening meal consisting of a soup, sandwich, salad, jacket potato and a hot dessert Increased number of choices at lunch time, with more hot options including a roast dinner option every day A new sandwich supplier providing a wider range of fillings Provision of more energy-dense options Increased range of snacks available including cakes, scones, thick and creamy and low-fat yoghurts, biscuits, fruit pots, cheese and crackers New printed menu folders displaying dietary coding including energydense options and information about accessing food outside of mealtimes Increased engagement of ward staff at mealtimes to help with meal service and assist patients Reinforcement of protected meal times Annual 'Making Mealtimes matter' campaigns to promote quality food service and provision Secured funding for a Food Services Dietitian to act as a link between dietitians, catering staff and ward teams (appointed August 2017) activity factors. A 10% stress factor was given for infection in the absence of pneumonia and septicaemia (34) to reduce overestimation. Protein requirements were calculated from estimated nitrogen requirements (33) .…”
Section: Estimated Individual Requirementsmentioning
confidence: 99%
“…Future research should aim to identify the barriers to screening in this setting because our previous work has shown that training alone is insufficient to achieve improved NST completion rates. Background: Many methods are available to determine energy requirements; however, all have limitations and their use in clinical practice is variable and not universally understood (Green et al, 2008). Estimating energy requirements of obese patients is particularly problematic (Breen et al, 2004).…”
mentioning
confidence: 99%
“…An opportunistic sample was recruited via e-mail providing a link to the survey (contact details openly available on NHS Trust websites) and through the online newsletter of the British Dietetic Association. The anonymous online questionnaire was developed specifically for this project by dietitians working in nutrition support and was based on the structure of two previous surveys (Reeves et al, 2003;Green et al, 2008). Respondents were asked to estimate energy requirements using two theoretical case scenarios: one patient was obese and one was not.…”
mentioning
confidence: 99%